Penggunaan Pembayaran Non Tunai Quick Response Code Indonesia Standard (QRIS) - Hasanuddin Hasanuddin; Andi Khaerun Nisa; Ferdiansyah Rini; Nurliah Nurliah (International Conference on Islamic Economic (ICIE), 2024)
The development of advanced technology and information will help the growth of the digital economy and accelerate the financial inclusion of a country. One form of implementation between information technology and digital economic growth includes non-cash transaction payments. So that people switch from conventional payments to digital payment models with the assumption that this digital payment model provides convenience and benefits. The purpose of this study is to determine what factors influence the ineffectiveness of the use of Non-Cash Quick Response Code Indonesian Standard (QRIS) payments by traders in Polewali Square, Polewali District, Polewali Mandar Regency. This type of research is qualitative research that builds meaning based on field data. This qualitative research procedure produces descriptive data in the form of written or spoken words from people and observable behavior. The results of the study indicate that the factors that influence the ineffective use of non-cash payments Quick Response Code Indonesian Standard (QRIS) by traders in the Polewali town square area, Polewali District, Polewali Mandar Regency are the lack of interest of traders and consumers to use the Quick Response Code Indonesian Standard (QRIS) as a means of payment in the town square area, the lack of socialization regarding QRIS, minimal knowledge about technological developments and the use of cash which is still the main means of payment among the community